Preventive strategies for low anterior resection syndrome: a protocol for systematic review and evidence mapping - Yang Li; Quan Wang; Xin-Yu Zhang; Ke-Lu Yang; Xiao-Nan Liu; Rui-Shu Li; Shi-Qi Wang (BMJ Open)
Introduction Rectal cancer is one of the top 10 cancers worldwide. Up to 80% of patients with rectal tumours have had sphincter-saving surgery, mainly due to the large expectation of anal preservation. However, patients tend to experience low anterior resection syndrome (LARS) after rectal resection, which is disordered bowel function that includes faecal incontinence, urgency, frequent defecation, constipation and evacuation difficulties. LARS, with an estimated prevalence of 41%, has been reported to substantially decrease the quality of life of patients. However, no comprehensive preventive strategies are currently available for LARS. This systematic review aims to synthesise evidence on the current LARS preventive strategies.Methods and analysis This protocol is reported according to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) checklist. Literature in PubMed (via Medline), Embase and the Cochrane Library from inception to July 2023 will be searched to identify articles relevant to preventive effectiveness against LARS. The Cochrane Collaboration’s risk of bias tool for randomised controlled trials and the Newcastle-Ottawa Scale for clinical controlled trials, cohort studies and case–control studies will be used to assess the risk of bias. We will group the included studies by the type of LARS prevention strategy and present an overview of the main findings in the form of evidence mapping. A meta-analysis is planned if there is no substantial clinical heterogeneity between the included studies. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) will be used to evaluate the quality of the evidence.Ethics and dissemination Ethical approval is not needed for systematic review of published data. The findings will be published in a peer-reviewed journal and disseminated at scientific conferences.PROSPERO registration number CRD42023402886.